Qualidade da fibra e diversidade genética em algodoeiro de fibra branca - Violatti, Marcela Ribeiro (2016)
The objective of this paper was to evaluate 19 genotypes of white fiber cotton related with eight intrinsic fiber characteristics to identify best crosses combinations, 2014/2015 and 2015/2016 seasons. The experiments were conducted in a randomized block design with 4 replicates in each season. A total of 19 cotton genotypes in (F5 and F6 generations) and two cultivars, DP 555 (Deltapine © Monsanto) and FM 966 (Fibermax © Bayer) were evaluated. After harvesting and processing of cotton seed, eight intrinsic characteristics of fibers were analyzed with help of High Volume Instrument (HVI): Micronaire index, fiber maturity, fiber length, uniformity index, elongation, short fiber index, and spin consistency index. The results of the analysis of variance of both seasons showed the existence of genetic variability regarding cotton fiber quality, with exception of the characteristics UI, SF, STR, ELG, in 2015/2016 season. By Scott-Knott's test for most characteristics in both seasons, genotypes were grouped into only two dissimilar groups. Genetic divergence was estimated from generalized distance of Mahalanobis and genotypes grouped by the Unweighted Pair Group Method with Arithmetic Mean (UPGMA) and non-hierarchical Tocher optimization method. By UPGMA method in the 2014/2015, cotton genotypes C, K and D were grouped separately in groups I, III and V, respectively. On other hand, by Tocher method, cotton genotypes K and C were classified in groups II and III, along with the commercial cultivars FM 966 and DP 555, being only genotype grouped alone, with highest average value of uniformity index and elongation of cotton fiber (86.25% and 6.73%, respectively). In 2015/2016, cotton genotypes J and H were grouped separately in groups II and V (UPGMA), V and VI (Tocher), independently of the methodology. In addition, cotton genotype D was grouped to genotype N, differently from the previous season, where it remained isolated from all other genotypes in both methods. UPGMA and Tocher methods were more effective in grouping cotton genotypes based on eight intrinsic characteristics associated with fiber quality. Due to their average performances at end of evaluations of eight intrinsic characteristics of cotton fiber in 2014/2015 and 2015/2016 seasons, cotton genotypes C and D are recommended for divergent crosses to obtain segregant populations with high fiber quality. The recombination between cotton genotypes that make up groups II, V and VI (UPGMA) and III and IV (Tocher) in the 2014/2015 season and groups I, IV and VI (Tocher), and I, IV and V (UPGMA) in the 2015/2016 season, will allow the expansion of favorable genetic variability, aiming at superior fiber quality.